Проблема підприємництва в економічній теорії - Горбачевська, О. В. (Видавництво Національного університету "Львівська політехніка", 2001)
Проведено аналіз зв’язків підприємництва з економічними дисциплінами: політичною економією, мікро- і макроекономікою. Зроблено рекомендації щодо вдосконалення їх викладання в закладах різного рівня акредитації. The analysis of the relationship between the problem ofentrepreneurship with economic subjects – political economy, micro- and macroeconomics in particular is carried out. The peculiarities ofentrepreneurship in Ukraine are specified. The author makes recommendations with regard to improvement of teaching economic subjects m training institutions of different levels of accreditation.